Obese Patients with Type 2 Diabetes on Conventional Versus Intensive Insulin Therapy: Efficacy of Low-Calorie Dietary Intervention. Issue 3 (March 2016) - Baltzis, Dimitrios; Grammatikopoulou, Maria; Papanas, Nikolaos; Trakatelli, Christina-Maria; Kintiraki, Evangelia; Hassapidou, Maria; Manes, Christos
Abstract Introduction The aim of this prospective study was to assess the results of a standard low-calorie dietary intervention (7.5 MJ/day) on body weight (BW) and the metabolic profile of obese patients with type 2 diabetes mellitus (T2DM) on intensive insulin therapy (IIT: 4 insulin injections/day) versus conventional insulin therapy (CIT: 2/3 insulin injections/day). Methods A total of 60 patients (n  = 60, 23 males and 37 postmenopausal females) were recruited and categorized into two groups according to the scheme of insulin treatment. Thirty were on IIT (13 males and 17 females) and an equal number on CIT (10 males and 20 females). BW, body mass index (BMI), HbA1c, and metabolic parameters were compared at 6 and 12 months after baseline. Results Significant reductions were observed in the BW, BMI, HbA1c (p  ≤ 0.001 for all) and cholesterol (p  ≤ 0.05) at 6 months post-intervention. At 1 year, median BW reduction was 4.5 kg (3.3, 5.8) for patients on IIT and 4.8 kg (3.6, 7.0) for those on CIT. The 12-month dietary intervention increased prevalence of normoglycemia in the IIT group and reduced the prevalence of obesity prevalence among the CIT participants (allp  < 0.001). CIT patients with BW reduction ≥5.0% demonstrated 11-fold greater chances of being normoglycemic (odds ratio 11.3, 95% CI 1.1–110.5). BW reduction ≥7.0% was associated with CIT, being overweight, and having normal HDLc, LDLc, and cholesterol levels. A reduction in BW between 5.0% and 6.9% was associated with IIT, normoglycemia, and obesity. Conclusion A 12-month 1800-kcal dietary intervention achieved significant BW and HbA1c reductions irrespectively of insulin regimen. CIT was associated with BW reduction greater than 8.0%, whereas IIT was associated with higher rates of normoglycemia.